Characterization of echolocation calls from insectivorous bats in Puting Bato Cave 5, Burdeos, Polillo island, Philippines - Taray, Kirk J.; Alviola, Phillip A.; Cruz, Florante A.; Lit, Ireneo L. Jr; Gonzalez, Juan Carlos T. (Vol. 150, No. 6B (December 2021) pages 1723-1734.)
"Acoustic recording is rarely applied in studying Philippine bats, which is reflected by the scarcity of related publications in the country. As a result, the echolocation calls of many local bat species are still unknown, and a reliable bat call library does not exist. Here, we described the echolocation call of some insectivorous bats in Polillo Island and used the call characteristics to define each species." - Abstract.